Factors Affecting Business Performance of Women Entrepreneurs in Malaysia - Wendy, Teoh Ming Yen (2008)
The objectives of this study are to understand the profile of women entrepreneurs in Malaysia as well as to explore and analyze the relationship between the influences of individual concepts towards their business performance. An in depth literature survey was conducted to identify a comprehensive list of factors influencing the performance of Malaysian women entrepreneurs. This resulted in the development of a comprehensive research framework which provides significant insights related to women entrepreneurship practices and their performance levels in Malaysia.